Shubnikov–de Haas Oscillations in Semiconductors at the Microwave-Radiation Absorption - G. Gulyamov; U. I. Erkaboev; A. G. Gulyamov (Advances in Condensed Matter Physics)
Mathematical models for the Shubnikov-de Haas oscillations in semiconductors are obtained at the microwave-radiation absorption and its temperature dependence. Three-dimensional image of microwave magnetoabsorption oscillations in narrow-gap semiconductors is established. Using a mathematical model, the oscillations of the microwave magnetoabsorption are considered for different values of the electromagnetic field. The results of calculations are compared with experimental data. The proposed model explains the experimental results in HgSe at different temperatures.